The Availability of Financial Resources Measured with Financial Slack for Exposing Carbon Emissions - Frans Giovanni Saputra; Retno Yulianti, Sri Hastuti (Proceeding International Conference on Accounting and Finance, 2025)
Climate change affected by carbon emission which results from industry of each countries currently be concern around the world because it could be threatening continuity life on earth. Many corporates are not exposed carbon emissions because need a lot of cost. Financial slack is the condition of adequate financial corporate so that could fund activity out of their obligatory. This research purposed to know financial slack effect to expose carbon emissions. The sample of this research is 24 coal corporates already listed in Indonesia Stock Exchange year of 2021-2023 so that total of observation is 72 observation. Analytical technique used on this research with Linear Regression Test. The research showing that financial slack gives positive influence to expose carbon emission on coal corporate which listed in Indonesia Stock Exchange. Thus, higher ratio of financial slack on corporate will enhance exposing carbon emissions. Higher financial slack will encourage corporate to act exposing carbon emissions because corporate has enough financial resources to fund activity out of obligatory as a responsibility the utilization of principal fund.